2020
DOI: 10.1038/s41598-020-76539-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological synchrony is associated with cooperative success in real-life interactions

Abstract: Cooperation is pivotal for society to flourish. To foster cooperation, humans express and read intentions via explicit signals and subtle reflections of arousal visible in the face. Evidence is accumulating that humans synchronize these nonverbal expressions and the physiological mechanisms underlying them, potentially influencing cooperation. The current study is designed to verify this putative linkage between synchrony and cooperation. To that end, 152 participants played the Prisoner’s Dilemma game in a dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 54 publications
3
47
2
Order By: Relevance
“…Even though our study did not provide evidence for singular interpersonal PS, other researchers showed signi cantly higher PS in original than in random pairings [45][46][47] . As PS is associated with emotional 48,49 , attachment and coregulatory processes 32 , this discrepancy to our study could be explained by the low emotional and social engagement involved in our tapping task.…”
Section: Discussioncontrasting
confidence: 96%
“…Even though our study did not provide evidence for singular interpersonal PS, other researchers showed signi cantly higher PS in original than in random pairings [45][46][47] . As PS is associated with emotional 48,49 , attachment and coregulatory processes 32 , this discrepancy to our study could be explained by the low emotional and social engagement involved in our tapping task.…”
Section: Discussioncontrasting
confidence: 96%
“…A laboratory study showed that synchronized movements can enhance memory for a social interaction (Macrae et al, 2008). Synchrony could facilitate effective cooperation in couples, allowing them to more successfully complete daily cognitive tasks such as managing finances (Behrens et al, 2020). Furthermore, couples who are in "sync" may have greater insight into each other's goals, which could be linked with promoting each other's goal pursuit and progress (Hoppmann & Gerstorf, 2013).…”
Section: Extending the Scope Of Synchrony To Other Areas Of Functioningmentioning
confidence: 99%
“…In the past years, this approach yielded promising insights in the behavioral and neural mechanisms underlying social interactions (Redcay & Schilbach, 2019 ). Recent findings successfully expanded an interactive viewpoint to the physiological level: Cooperation as a facet of prosocial behavior was found to be positively associated with two interactants’ synchronization in SCLs (Behrens et al, 2020 ). Synchrony in SCLs, as well as in heart rate, was further shown to be predictive of interpersonal attraction (Prochazkova et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%